Differential Impact of Environmental Policy Instruments on Technological Change: A Review of the Empirical Literature - Herman R.J. Vollebergh (Tinbergen Institute, 2006)
This survey reviews the empirical literature on the impact of environmental policy instruments on the rate and direction of technological change. The survey is explicitly focused on the empirical identification of the hypothesis to expect a stronger impact from market-based incentives than from non-market alternatives. The general picture emerging from the recent literature is that there is a clear impact of environmental policy on invention, innovation and diffusion of technologies. Although studies on a differential impact are still very scarce, the available evidence suggests that innovators look carefully for rent opportunities, which in turn depend on the specific incentives signalled by the type of (environmental) policy.
Keywords: Q38; Q55; Q58; 330; Environmental policy instruments; technological change; innovation; Umweltpolitik; Technischer Fortschritt; Wirkungsanalyse; Innovation; Innovationsdiffusion